Moneylender and the Welfare of Traders in Parung Market: Theological and Economic Approach - Ahmad Maulidizen; Heristina Fitri Rukmana; Muhammad Rafi Thoriq (AIBPM Publisher, 2022)
This research focuses on traders in Parung Market, aiming to discuss Moneylender and the welfare of traders in the Parung Market from theological and economic perspectives. The purpose of this study is: (1) to determine the existence of Moneylender in trading, (2) Moneylender from a theological perspective, and (3) to analyze the impact of Moneylender practices on the welfare of traders in Parung Market from an economic perspective. This research is a descriptive-qualitative research method with a critical paradigm approach in a case study research method. The primary data collection method is observation, structured interviews, and documentation. Data processing and analysis techniques are data reduction, data presentation, conclusion drawing, and verification. While testing the validity of the data is done by testing the credibility. This research’s findings indicate that Moneylender have existed since 2013 due to the need for capital and the absence of financial institutions that provide capital lending facilities. In addition, the mechanism for accounts payable is carried out with an easy process, but debt payments use the installment system daily. Moneylender harms the welfare of traders in Parung Market. From a theological perspective, the practice of usury by Moneylenders is not following the principles of Islamic economics, namely the principle of justice, the principle of Ta’awun, and Maslahat, so it does not meet the spiritual needs of traders. Meanwhile, from an economic perspective, capital loans from Moneylender can only meet capital needs for the short term and support the business being carried out because the interest charged to traders is very high